Facile MoS2 Growth on Reduced Graphene-Oxide via Liquid Phase Method - Tzitzios, Vasileios; Dimos, Konstantinos; Alhassan, Saeed M.; Mishra, Rohan; Kouloumpis, Antonios; Gournis, Dimitrios; Boukos, Nikolaos; Roldan, Manuel A.; Idrobo, Juan-Carlos; Karakassides, Michael A.; Basina, Georgia; Alwahedi, Yasser; et al. (Frontiers in Materials, 2018)
Single and few-layers MoS2 were uniformly grown on the surface of chemically reduced graphene oxide (r-GO) via a facile liquid phase approach. The method is based on a simple functionalization of r-GO with oleyl amine which seem to affect significantly the MoS2 way of growth. Scanning transmission electron microscopy (STEM) and Atomic Force Microscopy (AFM) analysis reveal the presence of single-layer MoS2 on the surface of a few-layers r-GO. XPS and Raman spectroscopies were used for in-depth structural characterization. Furthermore, we have successfully applied the method to synthesize MoS2 nanocomposites with multiwall carbon nanotubes (CN) and carbon nanofibers (CNF). The results demonstrate clearly the selective MoS2 growth on both carbon-based supports.